2018
DOI: 10.1038/s41598-018-22556-7
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Copper Oxide Nanoparticles Induces Pulmonary Toxicity and Fibrosis in C57BL/6 mice

Abstract: Copper oxide nanoparticles (CuO NPs) are widely used as catalysts or semiconductors in material fields. Recent studies have suggested that CuO NPs have adverse genotoxicity and cytotoxicity effects on various cells. However, little is known about the toxicity of CuO NPs following exposure to murine lungs. The purpose of this fundamental research was to investigate whether CuO NPs could induce epithelial cell injury, pulmonary inflammation, and eventually fibrosis in C57BL/6 mice. Our studies showed that CuO NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 40 publications
(39 reference statements)
2
58
0
Order By: Relevance
“…A two-week inhalation period affected the processes associated with apoptosis and programmed cell death. This result is comparable with the observations of Lai et al, who found time-and dose-dependence increased the intensity of the TUNEL-positive cells in the lung sections of mice, after the intranasal delivery of CuO NPs [20]. A six-week exposure period impacted on cell cycle-related processes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A two-week inhalation period affected the processes associated with apoptosis and programmed cell death. This result is comparable with the observations of Lai et al, who found time-and dose-dependence increased the intensity of the TUNEL-positive cells in the lung sections of mice, after the intranasal delivery of CuO NPs [20]. A six-week exposure period impacted on cell cycle-related processes.…”
Section: Discussionsupporting
confidence: 91%
“…Collagen, the major part of extracellular matrix, is fundamental to maintain the structure and function of the lungs. In a recent study, collagen accumulation, along with the expression of the progressive fibrosis marker α-SMA in the lungs of C57BL/6 mice exposed to CuO NPs by intranasal delivery, was detected [20] suggesting the possible induction of pulmonary fibrosis. Similarly, we also found the upregulation of α-SMA expression.…”
Section: Discussionmentioning
confidence: 95%
“…Augmented collagen production and induction of fibrosis can be associated with activation of myofibroblasts [27,28] and their expression of α-smooth muscle actin (α-SMA) [29]. Previous studies have reported the upregulation of α-SMA expression as a progressive fibrosis marker in the lungs after metal NP exposure [30,31].…”
Section: Figure 3: the Effect Of Pb(no3)2 Np Inhalation And Its Clearmentioning
confidence: 99%
“…Nanoparticles become a relevant noxious substances and their release from electronic devices and presence in the environment causes a potential risk for humans and lungs are one of the most endangered organs (167). In the recent experiment, toxicity of copper oxide nanoparticles intranasally administered was examined on 57BL/6 mice (168). The used copper nanoparticles induced pulmonary infl ammation resulting in fi brosis.…”
Section: Copper Nanoparticlesmentioning
confidence: 99%